2020
DOI: 10.1016/j.gore.2020.100624
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic cerebellar degeneration heralding recurrence of fallopian tube adenocarcinoma: A case report and literature review

Abstract: Highlights Paraneoplastic cerebellar degeneration in recurrence of fallopian tube cancer. Describes the initial symptoms of paraneoplastic cerebellar degeneration. Identify a diagnosis that can lead to rapid irreversible deterioration. Describe management and outcomes of paraneoplastic cerebellar degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…We found that ovarian or breast cancer was most commonly associated with Yo-PCD [13]. However, tubal and endometrial cancer were also observed with Yo-PCD, as described previously [6,14,15]. One man with PCD and unknown cancer tested positive for anti-Yo by all techniques.…”
Section: Discussionsupporting
confidence: 84%
“…We found that ovarian or breast cancer was most commonly associated with Yo-PCD [13]. However, tubal and endometrial cancer were also observed with Yo-PCD, as described previously [6,14,15]. One man with PCD and unknown cancer tested positive for anti-Yo by all techniques.…”
Section: Discussionsupporting
confidence: 84%